2018
DOI: 10.1002/path.5018
|View full text |Cite
|
Sign up to set email alerts
|

EBV‐encoded miRNAs target ATM‐mediated response in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a highly invasive epithelial malignancy that is prevalent in southern China and Southeast Asia. It is consistently associated with latent Epstein–Barr virus (EBV) infection. In NPC, miR‐BARTs, the EBV‐encoded miRNAs derived from BamH1‐A rightward transcripts, are abundantly expressed and contribute to cancer development by targeting various cellular and viral genes. In this study, we establish a comprehensive transcriptional profile of EBV‐encoded miRNAs in a panel of NPC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 57 publications
2
41
0
1
Order By: Relevance
“…ATM was initially recognized in individuals with ataxia telangiectasia, a neurodegenerative autosomal recessive disorder exhibiting motor neuropathy, immunodeficiency, and cancer predisposition . Several exogenous and endogenous factors regulate the kinase activity of ATM, including microRNAs (miRNAs) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ATM was initially recognized in individuals with ataxia telangiectasia, a neurodegenerative autosomal recessive disorder exhibiting motor neuropathy, immunodeficiency, and cancer predisposition . Several exogenous and endogenous factors regulate the kinase activity of ATM, including microRNAs (miRNAs) …”
mentioning
confidence: 99%
“…(12) Several exogenous and endogenous factors regulate the kinase activity of ATM, including microRNAs (miRNAs). (13,14) MicroRNAs are endogenous noncoding short RNA molecules that have been highly conserved during evolution. They generally bind to the 3′ untranslated region (UTR) of mRNAs and regulate many cellular processes, including metabolism, proliferation, differentiation, and apoptosis.…”
mentioning
confidence: 99%
“…In addition, in vitro animal experiments also indicate that EBV-miR-BART8-3p significantly increased the size of xenografts in nude mice and promotes radioresistance of NPC by regulating the activity of the ATM/ATR signaling pathway [63]. Studies have shown that the other four miRNAs encoded by EBV (BART5-5p, BART7-3p, BART9-3p and BART14-3p) directly target endogenous ATM, and the reduced ATM also helps maintain the virus incubation period [31,64]. MiR-24 expression was found to be decreased in nasopharyngeal carcinoma cells and patients with higher stage nasopharyngeal carcinoma, and this change was associated with the development of radiotherapy resistance [65,66].…”
Section: Mirnas Participate In Radiotherapy Resistance Of Nasopharyngmentioning
confidence: 99%
“…The hallmark of DNA double-strand break (DSB) is phosphorylation of histone H2AX in chromatin to produce γ-H2AX [30]. In eukaryotes, DNA damage is repaired after irradiation through DNA damage response (DDR) [31]. The repair of DNA damage greatly affects the survival of tumor cells, producing the resistance of radiotherapy.…”
Section: Mechanism Of Radiotherapy Resistance In Nasopharyngeal Carcimentioning
confidence: 99%
See 1 more Smart Citation